Post-Soeharto Indonesia : Renewal or Chaos? - Forrester, G., (sian Studies - Book Archive pre-2000., 1999)
Indonesia's economy has been ravaged by the Asian economic crisis. Its leader for 32 years, President Soeharto, was forced from office in May 1998 amidst rioting and student demonstrations. This book examines the political and economic trends which are shaping Indonesia's future. The contributors are leading politicians, business people, academics and international journalists with an intimate knowledge of Indonesia. Co-published with ISEAS.